Bioavailability and structural study of 20-hydroxyecdysone complexes with cyclodextrins - Temirgaziyev, Bakhtiyar S; Kučáková, Karolína; Baizhigit, Yerassyl A; Jurášek, Michal; Džubák, Petr; Hajdúch, Marián; Dolenský, Bohumil; Drašar, Pavel B; Tuleuov, Borash I; Adekenov, Sergazy M (Steroids, 2019)
20-Hydroxyecdysterone - (2β,3β,5β,22R)-2,3,14,20,22,25-hexahydroxycholest-7-en-6-one was isolated in satisfactory yield using ethanol extraction from the aerial part of Silene wolgensis (Hornem.) Otth; sometimes Silene wolgensis (Willd.) Bess. ex Spreng. The complexation of the phytoecdysteroid with β-cyclodextrin was studied by NMR spectroscopy. By studying the changes in chemical shifts of protons of substrates and receptors it was found that ecdysterone interacts with cyclodextrins to form supramolecular inclusion complexes of stoichiometric composition of 1:1 or 1:2. Ecdysterone-β-cyclodextrin complexes exhibit 100 times higher solubility in water than the parent compound.
Keywords: cyklodextriny; molekulární konformace; magnetická rezonanční spektroskopie; biologická dostupnost; Magnetic Resonance Spectroscopy; Ecdysterone; ekdysteron; Biological Availability; Solubility; Silene; rozpustnost; Molecular Conformation; Cyclodextrins